The dynamics of military coups in the contemporary Middle East: a structural perspective - Wenyuan Ma (Asian Review of Political Economy)
Abstract Military coups are the product of intense contradictions in civil-military relations. From 1931 to 2023, the Middle East witnessed at least 103 coups, which can be categorized into five periods: beginning, peaking, declining, ebbing, and resurging. Each marked by distinct characteristics. These coups can be classified into three types based on the identity of members: military faction-led coups, military faction-coordinated coups, and military faction-subordinate coups. Military elites led the former, whereas the latter two involved military elites, political elites, external members, and the public. This article finds that a military coup in the Middle East arises from various factors through a case study, including opportunities of success, strategic calculations of actors, and identity anxieties. Opportunities of success denote the possibility of a successful coup; strategic calculation of actors implies the cost–benefit assessments of military elites when launching a coup; and identity anxieties reflect military elites’ concerns about their status. The Syrian case demonstrates that, due to the high risk and cost involved, a military coup occurs when opportunities of success, strategic calculations of actors, and identity anxieties are present simultaneously.